Kecenderungan Kecurangan Pada BUMDes “Semangat Pemuda” Desa Giri Sasak Kecamatan Kuripan Kabpaten Lombok Barat - Fidianatun Fidianatun; Animah Animah; Yusli Mariadi (Valid: Jurnal Ilmiah, 2023)
The tendency of accounting fraud in terms of the system that occurs in BUMDes Semangat Pemuda in Giri Sasak village is caused by perpetrators misusing the information system used in BUMDes. Tendency of fraud is carried out by falsifying the number of transactions that are input into the system because the internal control system implemented at BUMDes Semangat Pemuda is not implemented properly.This study aims to reveal the form of accounting fraud in terms of the system using the Opportunity factor based on the Fraud Triagle Theory that occurs in BUMDes Semangat Pemuda. The method used in this research is descriptive with a qualitative approach. Data collection techniques using observation, interviews, and documentation. The results showed that the weak of BUMDe’s internal control system presented many loopholes fraud tendencies, including lack of proof of transactions, poor financial records, no separation of cash receipts and recording, not carrying out stock opname. Therefore, effective internal control will be very helpful in minimizing fraud and losses that occur.